Efforts to Improve Learning Outcomes in Football Games Passing through Wall Media at fifth Grade Students of Public Elementary School 122 Leboni - Poku, Ham; Hidayat, Rachmat; Nur, Suaib; Riswanto, A Heri (Universitas Negeri Semarang, 2024)
Passing drills using wall media are used as a tool for practicing passing in soccer games. In this study, the author aims to improve soccer passing learning outcomes. The research aims to determine the extent to which passing ability in soccer games can be improved through the use of wall media at elemtary school 122 Leboni. This study is classroom action research involving 15 fifth-grade students from elemtary school 122 Leboni as the research subjects. This Classroom Action Research (CAR) aims to improve passing ability in soccer games through the use of wall media. The research is designed in two cycles: Cycle I and Cycle II. In the design of this research, two cycles will be conducted, and each cycle consists of four stages: planning, action, observation, and reflection. The instruments used include the Learning Implementation Plan (RPP) and observation sheets. The RPP is used as a basis for the implementation of soccer learning practices using wall media. The focus of the research data is on passing ability, with the data source being fifth-grade students at elemtary school 122 Leboni. Based on the results and discussions presented, it shows that through the use of wall media, the passing ability in soccer games among fifth-grade students at elemtary school 122 Leboni has improved. Data analysis indicates a significant improvement in passing ability. In Cycle I, the passing success rate of fifth-grade students at elemtary school 122 Leboni was 67%, which increased to 100% in Cycle II. The conclusion is that the use of wall media is effective in improving students’ passing ability in soccer games.